Spatial income inequality in Brazil, 1872-2000 - Eustáquio Reis (EconomiA, 2014)
The paper provides historical perspectives on spatial economic inequalities in Brazil making use of a database on Brazilian municipalities from 1872 to 2000. A suit of maps and graphs describe the geographic factors shaping the historical development of the Brazilian economy highlighting the role of transport costs and its consequences for the spatial dynamics of income per capita and labor productivity. The remaining of the paper estimates econometric models of growth convergence for municipal income per capita and labor productivity. From 1920 onwards analyses are refined, firstly, by disaggregating the models for urban and rural activities; secondly, by assuming spatial correlation among variables of the model; and, thirdly, by enlarging the model to take account of the long run determinants of spatial growth convergence. Empirical results endorse the historical preeminence of geographic factors – in particular accessibility and transport conditions – as opposed to institutional conditions. The conclusion summarizes the results and proposes research extensions. – – O artigo analisa as desigualdades espaciais no Brasil em perspectiva histórica baseado em dados municipais sobre produç\~ao e populaç\~ao economicamente ativa de 1872 a 2000. Uma série de mapas e gráficos ilustram os fatores geográficos que condicionaram o desenvolvimento secular da economia brasileira destacando o papel dos custos de transporte e suas consequências para a dinâmica espacial. O cerne da análise é a estimaç\~ao de modelos econométricos de convergência municipal da produtividade do trabalho e da renda per capita no período de 1872 a 2000. Para os anos posteriores a 1920, a análise é refinada, primeiro, pela desagregaç\~ao dos modelos para as atividades rurais e urbanas. Segundo, pelo tratamento da correlaç\~ao espacial entre as variáveis do modelo. Terceiro, pela incorporaç\~ao das variáveis estruturais que condicionaram a convergência municipal da produtividade do trabalho e renda per capita. Os resultados empíricos salientam a importância de fatores geográficos, em particular os custos de transporte, vis-à-vis os fatores institucionais. A conclus\~ao sumaria os resultados e prop\~oe extens\~oes aprofundamentos da análise.
Keywords: O47; O55; R11; R12; N96; 330; Brazil; Transport cost; Cross-municipal growth convergence; Income per capita; Labor productivity; Spatial correlation; Geography versus institutions